Application of response surface methodology for chloride transport properties in nano metaclayed-UHPC - Mohd Faizal, Md Jaafar; Muhd Sidek, M. N.; Mohd Saman, H.; Khairunisa, Muthusamy; Norhaiza, Ghazali; Ibrahim, A. (Penerbit UMP, 2021)
The major concern on the deterioration of reinforced concrete structure is due to the corrosion of steel reinforcement from the aggressive environment such as chloride penetration. Ultra-high performance concrete (UHPC) is an advanced concrete material having ultra-high strength with excellent durability properties. Inclusion of nano metaclay in UHPC is expected to overcome the chloride transport properties in UHPC by providing nano filler effect. Two (2) assessments were conducted which are chloride content and chloride depth were examined. All the concrete specimens were immersed in 3% NaCl solution up to 365 days and the tests conducted were performed at 3, 7, 28, 56, 91, 182 and 365 days. Response surface method (RSM) was performed to evaluate the interaction and relationship between operating variables (compressive strength and nano metaclay content). Based on RSM analysis, inclusion of nano metaclay in UHPC have good relationship towards the chloride resistance characteristics and adequate durability performance in terms of chloride penetration resistance. The results exhibited that inclusion of 1% nano metaclay significantly and positively affect in term of chloride penetration resistance.